POLITIK HUKUM PENYATUAN KELEMBAGAAN LITBANG JIRAP DAN IMPLIKASINYA BAGI KELEMBAGAAN DAN PENATAAN SDM : Legal Politics of Institutional Unification Research and Development Institution and its Implications for Institutional and Human Resources Management - Safira Annisa (Constitution Journal, 2022)
The establishment of BRIN as a mandate to implement Law Number 11 of 2019 concerning to National System of Science and Technology brings renewal to the institutional form of research and development in Indonesia. This study aims to find out the legal politics of uniting research and development institutions through BRIN and its implications in the context of institutional arrangements and human resources. This research uses a normative juridical method with statutory approaches, conceptual approaces, and case approaches. The results of the research show: first, the legal politics of uniting research and development institutions is based on the mandate of the National Science and Technology National Agency Law which aims to strengthen the carrying capacity of science and technology as an integrated institution carrying out research, development, study and application as well as inventions and innovations; and second, the implications of the results of the unification of research and development institutions through BRIN have an impact on the transfer of duties, functions and authorities of existing research and development institutions in ministries/institutions and independent institutions as well as the transfer of the human resources status of researchers from various ministries and institutions into BRIN employees. Keywords: BRIN, integration, research, innovation, research and development. Pembentukan BRIN sebagai mandat pelaksanaan Undang-Undang Nomor 11 Tahun 2019 tentang Sistem Nasional Ilmu Pengetahuan dan Teknologi Iptek membawa pembaharuan pada bentuk kelembagaan lembaga litbang jirap di Indonesia. Penelitian ini bertujuan untuk mengetahui politik hukum penyatuan kelembagaan litbang jirap melalui BRIN dan implikasinya dalam konteks penataan kelembagaan dan sumber daya manusia. Penelitian ini menggunakan metode yuridis normatif melalui studi kepustakaan dengan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus. Hasil penelitian menunjukkan: pertama, politik hukum penyatuan kelembagaan litbang jirap didasarkan pada mandat Undang-Undang Sisnas Iptek BRIN yang bertujuan untuk memperkuat daya dukung iptek sebagai lembaga yang secara terintegrasi menjalankan penelitian, pengembangan, pengkajian dan penerapan serta invensi dan inovasi; dan kedua, implikasi hasil penyatuan lembaga litbang jirap melalui BRIN berdampak terhadap pengalihan tugas, fungsi, dan wewenang lembaga litbang jirap existing di kementerian/lembaga dan lembaga independen serta pengalihan status kepegawaian para peneliti menjadi pegawai BRIN. Kata kunci: BRIN, integrasi, riset, inovasi, penelitian dan pengembangan.